Novel composite polymer-amended bentonite for environmental containment: Hydraulic conductivity, chemical compatibility, enhanced rheology and polymer stability. (16th May 2023) - Fu, Xian-Lei; Zhuang, Heng; Reddy, Krishna R.; Jiang, Ning-Jun; Du, Yan-Jun
Graphical abstract: Highlights: Novel composite polymer-amended bentonite is developed. PAC-HPMC mass ratio for bentonite amendment is optimized. Amended bentonite possesses superior k when exposed to Cd(NO3 )2 solution. Yield stress is a viable indicator for evaluating polymer stability in amended bentonite. Abstract: This study developed a novel composite polymer-amended bentonite consisting of two linear polymers (i.e., polyanionic cellulose (PAC) and hydroxypropyl methylcellulose (HPMC)) for use as an engineered barrier material in environmental containment applications. Several series of laboratory experiments were conducted on bentonite and polymer-amended bentonites with different PAC-HPMC mass ratios to evaluate free swell index and liquid limit using deionized water and 20 mM cadmium nitrate (Cd(NO3 )2 ) as a typical contaminant. Hydraulic conductivity of bentonite and polymer-amended bentonite filter cakes was determined via modified fluid loss (MFL) tests using 20 mM Cd(NO3 )2 solution under increasing pressure conditions. Rheological properties, such as apparent viscosity and shear stress, were measured, and yield stresses were estimated using the Bingham plastic and Herschel–Bulkley models to evaluate polymer stability. The results showed that exposure to 20 mM Cd(NO3 )2 solution reduced both free swell index and liquid limit of bentonites with and without polymer-amendment. The bentonite amended with PAC-HPMC mass ratio of 7 (i.e., (P7H1)B) possessed the lowest hydraulic conductivity among the bentonites tested. Its hydraulic conductivity was one to two orders of magnitude lower than that of unamended bentonite. The ultraviolet absorption spectra analyses revealed the value of the wavelength of maximum absorption bands for (P7H1)B slurry was 11.9% greater than that for PAC-amended bentonite slurry, indicating stronger hydrogen bonding strength of (P7H1)B slurry. The total organic carbon in the filtrate for HPMC-amended bentonite slurries was 64.0–67.7% lower than that for PAC-amended bentonite slurries in the MFL tests. In addition, the total organic carbon in the filtrate decreased with increasing yield stress of polymer-amended bentonite slurries, indicating yield stress can be used as a good indicator for evaluating polymer stability in the polymer-amended bentonite filter cakes.